2020
DOI: 10.1093/humrep/deaa159
|View full text |Cite
|
Sign up to set email alerts
|

DNA fragmentation of sperm: a radical examination of the contribution of oxidative stress and age in 16 945 semen samples

Abstract: STUDY QUESTION What is the relationship between sperm DNA fragmentation and oxidative stress (OS) with increasing male age? SUMMARY ANSWER Sperm DNA fragmentation increases with age and is likely related to both defective spermatogenesis and increasing OS levels. WHAT IS KNOWN ALREADY Sperm quality declines with age. The presence of DNA damage in a high fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 70 publications
6
44
2
2
Order By: Relevance
“…This correlation has also been reported in males with subclinical, normozoospermic, asthenozoospermic and oligozoospermic varicocele [ 40 ]. Linear correlations between SDF and seminal OS with increasing paternal age [ 41 ] have also been noted. However, it is suggested that both SDF and another measure of OS should be used in the evaluation of infertile men [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This correlation has also been reported in males with subclinical, normozoospermic, asthenozoospermic and oligozoospermic varicocele [ 40 ]. Linear correlations between SDF and seminal OS with increasing paternal age [ 41 ] have also been noted. However, it is suggested that both SDF and another measure of OS should be used in the evaluation of infertile men [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sperm apoptosis, this data is in accord with some observations made in testes of old mice that showed low apoptotic frequencies than young adults 48,49 , however the correlation between aging and sperm DNA integrity represents another controversial question. Using different methods of investigations, it was suggested a detrimental effect of advanced paternal age on sperm chromatin integrity or DNA fragmentation 17,18,50,51 . TEM analysis enabled to clearly discriminate the chromatin status (uncondensed, disrupted and with holes) evaluating at same time different sperm characteristics as acrosome, plasma membrane, mitochondria, axoneme, and, after mathematical elaboration, it indicated that the chromatin damage was especially referred to necrosis more than apoptosis and immaturity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also considered the possibility of age-related changes in sperm genetics, such as sperm DNA fragmentation [16][17][18] , sperm aneuploidy 19 , telomere length 20 and epigenetics 21 . Moreover, an increased risk of congenital abnormalities, neuropsychiatric diseases 6 , autism 22 and childhood acute lymphoblastic leukemia 23 in offspring of men with advanced paternal age have been described.…”
mentioning
confidence: 99%
“…DNA fragmentation is a well-examined condition related to male infertility [ 251 ]. DNA fragmentation in a semen sample is correlated with diminished fertility and reduces the probabilities of natural conception and intrauterine insemination success [ 252 ], as the presence of high levels of DNA damage lead to embryonic arrest. It has been established that sperm DNA integrity affects fertilization rate, developmental arrest, and live birth rates [ 253 ].…”
Section: Resultsmentioning
confidence: 99%